Frequencies and phenotypes of p24 + cells following PMA/Tat_LNP stimulation. (A-D) CD4 T cells from Acute UD, Acute UD + 5, Chronic UD and Chronic UD + x individuals were stimulated for 24h with PMA/Tat_LNP (A) Frequencies of p24 + cells in CD4 T cells. Median values are plotted. Open circles represent limit of detection (LOD). (B) Percentages of HIV-infected cells expressing the p24 protein following stimulation. Median values are plotted. Participants with an LOD frequency of p24 + cells in CD4 T cells or unreportable/unavailable total HIV DNA quantification were not included in this analysis. (C) Frequencies of cells with a given phenotype (TN, TCM/TTM, TEM, TTd) in p24+ and p24- fractions. Participants with a minimal number of 4 p24 + cells are represented. Grey bars depict median values. (D) Proportions of all p24 + cells with a given phenotype (TN, TCM/TTM, TEM, TTd). p24 + cells ( - Tine Struyve (22683295) (2025)
Frequencies and phenotypes of p24 + cells following PMA/Tat_LNP stimulation. (A-D) CD4 T cells from Acute UD, Acute UD + 5, Chronic UD and Chronic UD + x individuals were stimulated for 24h with PMA/Tat_LNP (A) Frequencies of p24 + cells in CD4 T cells. Median values are plotted. Open circles represent limit of detection (LOD). (B) Percentages of HIV-infected cells expressing the p24 protein following stimulation. Median values are plotted. Participants with an LOD frequency of p24 + cells in CD4 T cells or unreportable/unavailable total HIV DNA quantification were not included in this analysis. (C) Frequencies of cells with a given phenotype (TN, TCM/TTM, TEM, TTd) in p24+ and p24- fractions. Participants with a minimal number of 4 p24 + cells are represented. Grey bars depict median values. (D) Proportions of all p24 + cells with a given phenotype (TN, TCM/TTM, TEM, TTd). p24 + cells (